Ringgit/Yuan Exchange Rate And Its Implications On Malaysia’s Trade With China And Selected Trading Partners: Evidence From Industry Data - Soleymani, Abdorreza (2014)
China is the largest trading partner of Malaysia today. However, trade volume between these two countries can be strongly influenced by exchange rate fluctuations. There is also competition between Malaysia and other developing East Asian countries in the Chinese market due to the similarity of economic structures and export commodity. These concerns are crucial for the Malaysian economy, since decreasing trade deficit and increasing trade volumes with China, are very important to GDP growth, export earnings, investment and employment in Malaysia. This thesis investigates the effect of ringgit/yuan on trade between Malaysia and China at industry level by employing autoregressive distributed lag cointegration analysis and using disaggregated bilateral import and export industry annual data at three-digit Standard International Trade Classification level over the 1985-2010 period. First, currency depreciation effect is isolated to investigate the real ringgit/yuan sensitivity to 39 import and 39 export industries between Malaysia and China. The results reveal that most of the industries are sensitive to the real bilateral exchange rate in the short-run. The short-run effect shifts into the long-run in 46% industries in outpayment models and in 37% industries in inpayment models. The results also imply that a one percent real depreciation improves Malaysian trade balance by 7.45 percent. Second, the direct effect of real ringgit/yuan volatility on 151 Malaysian imports and 24 Malaysian export industries with China is investigated.